A Heparan Sulfate-Binding Cell Penetrating Peptide for Tumor Targeting and Migration Inhibition. (3rd May 2015) - Chen, Chien-Jung; Tsai, Kang-Chiao; Kuo, Ping-Hsueh; Chang, Pei-Lin; Wang, Wen-Ching; Chuang, Yung-Jen; Chang, Margaret Dah-Tsyr
Abstract : As heparan sulfate proteoglycans (HSPGs) are known as co-receptors to interact with numerous growth factors and then modulate downstream biological activities, overexpression of HS/HSPG on cell surface acts as an increasingly reliable prognostic factor in tumor progression. Cell penetrating peptides (CPPs) are short-chain peptides developed as functionalized vectors for delivery approaches of impermeable agents. On cell surface negatively charged HS provides the initial attachment of basic CPPs by electrostatic interaction, leading to multiple cellular effects. Here a functional peptide (CPP ecp ) has been identified from critical HS binding region in hRNase3, a unique RNase family member with in vitro antitumor activity. In this study we analyze a set of HS-binding CPPs derived from natural proteins including CPP ecp . In addition to cellular binding and internalization, CPP ecp demonstrated multiple functions including strong binding activity to tumor cell surface with higher HS expression, significant inhibitory effects on cancer cell migration, and suppression of angiogenesis in vitro and in vivo . Moreover, different from conventional highly basic CPPs, CPP ecp facilitated magnetic nanoparticle to selectively target tumor site in vivo . Therefore, CPP ecp could engage its capacity to be developed as biomaterials for diagnostic imaging agent, therapeutic supplement, or functionalized vector for drug delivery.